(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
In recent years, Geographic Information Systems (GIS) have been gaining strength in many areas of knowledge due to its versatility and ability to analyze, edit and view information related to a geographical area. This article presents ECOGIS, a query tool of ecological and circulating flows in Quindio River basins. This database was created with the GIS ARCGIS 9.3. Environmental flows have been estimated using hydrologic and hydraulic methodologies and classified according to the time (Annual and Monthly) and methodologies implemented in Colombia. Circulating flows are products of hydrological modeling Quindío river basin in the SSD WEAP. With this tool, ECOGIS, water resource planners may make conqueries, generate reports and produce graphs of stored information relating to environmental flows and circulating at any time ; these activities can be performed on any stretch and/ or point of interest on the bed of Quindío River.